Vietnamese natural language processing for interaction between human and robot - Luong Huu Thanh Nam; Nguyen Dao Xuan Hai; Tuong Phuoc Tho; Nguyen Truong Thinh (Journal of Technical Education Science, 2019)
Service robot has been designed and developed for different objectives and requirements. Since the robotic revolution, Vietnam is one of the most influenced among South-east Asia countries in developing artificial intelligence. People believe that robot will replace all blue-collars in almost company, even hospital and school in the next few decades, therefore developers are trying to improve natural language interaction between human and robot, especially helping new vision for Vietnamese robotics. We have built a robot application that capable of understanding Vietnamese natural language, there are four tasks which were mentioned solving the problems, even more AI method. Deep learning, on the other hand, is a sub-field of machine learning. In this paper, with these algorithms, artificial intelligent supported is much complex, people can communicate naturally with robot, not only English but also Vietnamese as well. In this paper, we will introduce the specification and intelligent interaction processing in naturally Vietnamese.